Pemanfaatan Event Car Free Day (CFD) Dan Peningkatan Kualitas Produk Dalam Meningkatkan Perekonomian UMKM Lokal Di Banyuwangi - Laili, Desi Jumatul; Kholisah , Nur; Akbar , Achmad Syarif (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2025)
This study aims to analyze the utilization of the Car Free Day (CFD) event and product quality improvement in enhancing the local MSME economy in Banyuwangi. The research employs a descriptive qualitative approach using data collection methods including interviews, observations, and documentation involving MSME actors, event organizers, and visitors at the CFD event on Ahmad Yani Street, Banyuwangi. The findings indicate that CFD serves as an effective direct marketing platform, reflected in increased sales, expanded customer networks, and strengthened MSME branding. However, income growth tends to be fluctuative and depends on visitor volume and product attractiveness. Improvements in product quality particularly in taste, hygiene, consistency, and packaging significantly enhance customer satisfaction and encourage repeat purchases. Therefore, the effective utilization of CFD, supported by continuous product quality improvement, contributes positively to the sustainable economic growth of local MSMEs in Banyuwangi.